Variabilidad génetica mediante caracterización morfológica en achiote (Bixa orellana L.) para fines de mejoramiento. Zungarococha. San Juan. 2020 - Inuma Rios, Marcelo de Jesus (2022)
The current research work aims to provide information for upcoming breeding programs through morphological characterization in eight morphotypes of Bixa orellana L. It was conducted in the workshop of teaching and research in Amazonian medicinal crops of the Faculty of Agronomy, with U.T.M. coordinates in longitude in the West: W 73° 22’ 10.4" LS, S 03° 50’ 13.2; and with an altitude: 118 meters above sea level. Province of Maynas - District of San Juan Bautista. The research was descriptive and cross-sectional. The sample consisted of 40 plants of eight morphotypes of achiote, taking 05 plants per accession and 03 as a sample. According to the results, it is concluded that the qualitative morphological descriptors show that there is phenotypic variability in the eight morphotypes of achiote, mainly in the color of the leaf, flower, and stamen, shape of the fruit apex, fruit base, capsule, dehiscence, pigmentation tone and thorniness. According to the Jaccard similarity index, the least distant morphotypes according to their variability profile are M6 and M5 with 0.71, M10 and M11 with 0.75 and 0.75 for morphotypes M4 and M2. According to the principal component analysis for the quantitative descriptors, in CP1 the descriptors that contributed positively to variability were spine length with 0.84, 100-seed weight with 0.84 and number of seeds with 0.64. In CP2, number of stamens with 0.90 and number of seeds with 0.71 dominated in positive contribution and plant height with -0.70 in negative contribution. The percentage of bixin is separated from the other quantitative descriptors so that the greatest variability of the descriptors is concentrated in this variable, associated with this variable are the morphotypes M11 and M10.